Comparison of palonosetron-dexamethasone and ondansetron-dexamethasone for prevention of postoperative nausea and vomiting in middle ear surgery: a randomized clinical trial - Srivastava,Vinit Kumar (2020)
Abstract Background: Postoperative nausea and vomiting is the second most common complaint in the postoperative period after pain. The incidence of postoperative nausea and vomiting was 60-80% in middle ear surgeries in the absence of antiemetic prophylaxis. Because of this high incidence of postoperative nausea and vomiting, we aimed to assess the effect of palonosetron-dexamethasone and ondansetron-dexamethasone combination for the prevention of postoperative nausea and vomiting in patients of middle ear surgery. Methods: Sixty-four patients, scheduled for middle ear surgery, were randomized into two groups to receive the palonosetron-dexamethasone and ondansetron-dexamethasone combination intravenously before induction of anesthesia. Anesthesia technique was standardized in all patients. Postoperatively, the incidences and severity of nausea and vomiting, the requirement of rescue antiemetic, side effects and patient satisfaction score were recorded. Results: Demographics were similar in the study groups. The incidence difference of nausea was statistically significant between groups O and P at a time interval of 2-6 hours only (p = 0.026). The incidence and severity of vomiting were not statistically significant between groups O and P during the whole study period. The overall incidence of postoperative nausea and vomiting (0-24 hours postoperatively) was 37.5% in group O and 9.4% in group P (p = 0.016). Absolute risk reduction with palonosetron-dexamethasone was 28%, the relative risk reduction was 75%, and the number-needed-to-treat was 4. The patient’s satisfaction score was higher in group P than group O (p = 0.016). The frequency of rescue medication was more common in group O than in group P patients (p = 0.026). Conclusion: The combination of palonosetron-dexamethasone is superior to ondansetron-dexamethasone for the prevention of postoperative nausea and vomiting after middle ear surgeries.